Caracterização de práticas de governança territorial no processo de desenvolvimento contemporâneo em Timor-Leste: análise a partir da questão da formação profissionalizante - Moraes, Gabino Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The departure point of this thesis was to highlight the enormous challenges faced by Timor-Leste to professionalize the youth of the country, taking into account the importance of these initiatives for the economic development and the construction of territorial equity. The capital relevance of these initiatives in this context is related to the demographic condition of the small country that has predominantly a young population. This question points out to the need of the country to produce alternatives for the territorial development, with a comprehension of the role of local initiatives and of the international cooperation of global social actors, which are in the territory with its diverse subsidiary scales and its intrinsic conditionalities. The main objective of this thesis is to analyse the policies for the professional training of youth, which have been implemented in Timor- Leste, with a focus on the vocational education, looking at the main initiatives of the National Secretary for Professional Training and Employment of Timor-Leste and the network of governance of this institution with different social actors that have been in Timor-Leste since its independence. The approach presented here is connected with the analysis of territorial dynamics and the ways that the question of development is related to the question of territorial governance, this means to understand the articulation of public policies and of territorial organization as sources for development. The methodology of the research was based in statistical techniques, cartographic overlapping, fieldwork to make interviews with the local social actors and at the end the content analysis of the data gathered in the field. The conclusion of this investigation is that there is an overlapping of social actors in terms of multilevel governance in Timor-Leste and that the professional training of the youth for the country contributes to the improvement of the qualifications...

O ponto de partida desta tese foi sublinhar os enormes desafios que Timor-Leste tem enfrentado em profissionalizar a juventude do país, tendo em vista a importância dessas iniciativas no desenvolvimento econômico e na construção de equidade territorial. A relevância capital dessas iniciativas nesse contexto relaciona-se à condição demográfica do pequeno país que tem uma população predominantemente jovem. Essa problemática coloca a necessidade de produzir alternativas para o seu desenvolvimento territorial, compreendendo devidamente o papel das iniciativas que estão sendo construídas localmente e da cooperação de atores sociais globais presentes no território com suas diferentes escalas de subsidiariedade e suas condicionalidades intrínsecas. O objetivo desta tese é analisar as políticas públicas para o aperfeiçoamento da juventude que estão implementadas em Timor-Leste, com enfoque no ensino técnico-vocacional, a partir das principais ações da Secretaria de Estado para a Política de Formação Profissional e Emprego e das suas redes de governança construída com os atores sociais presentes em Timor-Leste desde a sua independência. Nossa abordagem vincula-se à análise das dinâmicas territoriais e à forma como tem sido pensada a questão do desenvolvimento, a partir dos princípios da governança territorial, ou seja, da articulação entre o plano das políticas públicas e do ordenamento do território como vetores do desenvolvimento. A metodologia utilizada empregou técnicas estatísticas, sobreposição cartográfica, trabalho de campo, para realizar entrevistas com atores sociais, e posterior análise de conteúdo dos dados obtidos em campo. Ao final da tese, conclui-se que há uma sobreposição de agentes sociais em governança multinível em Timor-Leste e que profissionalizar a juventude do país contribui para o aperfeiçoamento da população jovem, constituindo-se como um fator de desenvolvimento...
Keywords: Human geography; Geografia humana; Politicas publicas; Governança; Formação profissional; Juventude - Emprego; Planejamento urbano; Timor Leste